Sancho y Madridejos : 66 viviendas en Carabanchel (2003)
Proyectos de intervenciones para los <Juegos Olímpicos> 2012 en Madrid.
Keywords: MADRID; ESPAÑA; VIVIENDAS MULTIFAMILIARES; PROYECTOS; INTERVENCIONES; MADRIDEJOS, SOL; SANCHO OSINAGA, JUAN CARLOS; MADRIDEJOS/SANCHO